2014
DOI: 10.3389/fevo.2014.00025
|View full text |Cite
|
Sign up to set email alerts
|

Color contrast and stability as key elements for effective warning signals

Abstract: Vivid warning signals (aposematism) have evolved repeatedly throughout the animal kingdom. However, relatively few studies consider what makes an effective signal, in terms of preventing attack and promoting avoidance learning by predators. Signal form varies substantially among and sometimes within species, but there has also been apparent convergence on relatively few main color types. We aimed to determine why warning signals often combine red, orange, yellow, and black colors, and specifically to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 86 publications
1
65
1
1
Order By: Relevance
“…Illuminant colour can be measured from the relative ratios of the linear RGB values, or, if exposure time is controlled for the intensities between photographs can also be measured (see Lovell et al . and Arenas, Troscianko & Stevens ).…”
Section: Normalisationmentioning
confidence: 97%
“…Illuminant colour can be measured from the relative ratios of the linear RGB values, or, if exposure time is controlled for the intensities between photographs can also be measured (see Lovell et al . and Arenas, Troscianko & Stevens ).…”
Section: Normalisationmentioning
confidence: 97%
“…Field studies with model frogs and ladybirds have shown that chromatic contrast to the natural background is particularly important (Arenas et al., ; Hegna, Saporito, Gerow, & Donnelly, ), while experiments presenting different species of Lycaeidae seed bug larvae to domestic chicks suggest that prey with redder and more saturated signals are more strongly avoided (Gamberale‐Stille & Tullberg, ). Long‐wavelength colours are also thought to be more effective as warning signals, due to innate avoidance by some predators and their greater stability under different lighting conditions (Arenas, Troscianko, & Stevens, ). Finally, experiments with artificial stimuli and natural prey items such as Arctia plantaginis (wood tiger moth) larvae suggest that larger coloured markings generate greater avoidance (Forsman & Merilaita, ; Lindstedt, Lindström, & Mappes, ; Lindström, Alatalo, Mappes, Riipi, & Vertainen, ; Smith, Halpin, & Rowe, ).…”
Section: Discussionmentioning
confidence: 99%
“…Higher signal stability may be due to the fact that both red and yellow are colours with longer wavelengths and thus, are less susceptible to scattering by atmospheric particles. As such, they are perceived as more uniform and stable colours across the time of day [51]. Atmospheric particles and cloud cover tend to scatter shorter wavelengths through the process of Rayleigh scattering, thus negatively affecting the stability of a signal [51].…”
Section: Discussionmentioning
confidence: 99%
“…As such, they are perceived as more uniform and stable colours across the time of day [51]. Atmospheric particles and cloud cover tend to scatter shorter wavelengths through the process of Rayleigh scattering, thus negatively affecting the stability of a signal [51]. In addition, signal contrast against the natural habitat of the prey, which tends to be green vegetation, is theorized to contribute to aposematic signal effectiveness [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation